SITTING IN AN ERGONOMIC CHAIR TO AVOID LOW BACK PAIN IN WORKERS - Gempur Santoso (International Journal of Social Science, 2026)
This paper focuses on the occurrence of low back pain due to prolonged sitting in a chair. This paper is designed descriptively. Data is then collected from various ergonomics experts and research, and the analysis also uses descriptive methods. In conclusion, an ergonomic chair must have a backrest, a chair that can be adjusted up and down, have five wheelchair legs, a chair with stable armrests or elbow rests, a chair with a stable footrest, and a rest after sitting for 30 to 60 minutes. The chair must be able to be used loosely or freely. Using an ergonomic chair will prevent low back pain. It is recommended that factories that employ workers or whose work involves sitting in chairs use ergonomic chairs to avoid low back pain.